2012
DOI: 10.1002/polb.23035
|View full text |Cite
|
Sign up to set email alerts
|

Advanced materials based on polymer cocrystalline forms

Abstract: Polymeric ''cocrystalline forms,'' that is, structures were a polymeric host and a low-molecular-mass guest are cocrystallized, were early recognized, and in many cases also well characterized by X-ray diffraction studies. However, only in the last two decades cocrystalline forms have received attention in material science, due to the ability (of few of them) to maintain an ordered polymer host structure even after guest removal, thus leading to the formation of ''nanoporous-crystalline forms,'' for which many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 193 publications
(340 reference statements)
7
123
1
Order By: Relevance
“…The reason for this difference resides in the presence of a dense layer that covered the films developed by Yokoyama et al [54]. Finally, Rizzo et al [234] and Guerra and coworkers [184] found that s-PS films (thickness % 20 lm; pore size % 1 nm; porosity: 7%) exhibited chiral optical responses both in the infrared and in the UV-visible regions, opening the opportunity to achieve s-PS-based films with tunable chiral optical properties. Thus, nanoporous polymers seem to present enhanced optical behavior compared to the solid, which is mainly governed by the porosity of the system and not by the pore size.…”
Section: Nmmentioning
confidence: 98%
See 1 more Smart Citation
“…The reason for this difference resides in the presence of a dense layer that covered the films developed by Yokoyama et al [54]. Finally, Rizzo et al [234] and Guerra and coworkers [184] found that s-PS films (thickness % 20 lm; pore size % 1 nm; porosity: 7%) exhibited chiral optical responses both in the infrared and in the UV-visible regions, opening the opportunity to achieve s-PS-based films with tunable chiral optical properties. Thus, nanoporous polymers seem to present enhanced optical behavior compared to the solid, which is mainly governed by the porosity of the system and not by the pore size.…”
Section: Nmmentioning
confidence: 98%
“…However, new systems, such as polymers of intrinsic microporosity (PIMs) (rigid macromolecules that form nanoporous organic materials because of their inability to pack space efficiently [175]) [176][177][178][179], hypercrosslinked polymers [180][181][182], amorphous conjugated microporous polymers (CMPs) [183], and polymeric cocrystalline forms [184], have emerged to overcome these problems. For instance, McKeown et al [176] and later Budd and coworkers [177] developed different PIMs systems with pore widths between 0.6 and 0.7 nm (the density and membrane thickness were not specified).…”
mentioning
confidence: 99%
“…Molecular volumes of the investigated molecules were calculated using winmostar. SP value of SPS is calculated to be 10.4 (cal/cm 3 and d intercalate (E, F) phase. As a reference, two typical WAXD patterns of SPS/guest d clathrate co-crystalline phase (A 0 ) and SPS/ guest d intercalate co-crystalline phase (F 0 ) are also shown in Fig.…”
Section: Determination Of Gel Morphology Of Sps/solvent Systemsmentioning
confidence: 99%
“…[1][2][3][4][5] In this paper we apply different computational techniques, along with experimental measures, to obtain a reliable atomistic structure for a recently synthesized hypercrosslinked polymer, with a peculiar porous structure and very interesting adsorption capacities for methane and carbon dioxide. 6 Nanoporous materials are of great interest for applications in gas storage, 7-9 molecular separation, [10][11][12] heterogeneous catalysis, [13][14][15] and the properties of such materials are critically affected by their porous structure, whose main parameters are the specific surface area, the micro-and mesoporous volumes and the pore size distribution. Remind that, according to the IUPAC rules, nanopores are classified as ultramicropores (with pore diameter below 0.7 nm), micropores (pore diameter between 0.7 and 2 nm) 65 and mesopores (between 2 and 50 nm).…”
Section: Introductionmentioning
confidence: 99%